Major and trace element geochemistry of granitic augen gneisses from Tamakoshi-Likhu Khola area, east Nepal - Regmi, KR (Journal of Nepal Geological Society, 2008)
The Himalaya, originating from the collision of India and Eurasia, is characterised by a widespread occurrence of peraluminous granitic rocks of different ages at different structural and tectonic levels. In the Tamakoshi-Likhu Khola area, east Nepal granitic augen gneisses are exposed in the Higher Himalayan (HH) crystallines, footwall of the Main Central Thrust (MCT) and core of Lesser Himalayan (LH) dome. Major and trace element whole rock geochemistry, and mineral chemistry of selected minerals, particularly K-feldspar (Kfs), plagioclase (Pl), garnet (Grt), biotite (Bt), muscovite (Ms), and tourmaline (Tur) were investigated in these augen gneisses. The gneisses show high mol. A/CNK values (i.e., 1.62-2.04 in HH, 1.6-2.7 in MCT footwall and 1.68-2.14 in LH dome gneisses) indicating their peraluminous nature. The HH gneisses show lowest average SiO2, and highest TiO2, total FeO, CaO and Na2O contents. K2O/Na2O in these gneisses is variable (0.27-2.23, 0.42-3.62 and 0.21-2.21 respectively in the HH, MCT footwall and LH dome gneisses). The gneisses are characterised by high Rb (78-378 ppm in the HH, 118- 716 ppm in the MCT footwall and 164-510 ppm in the LH dome gneisses) and low Sr (50-308 ppm in the HH, 8-97 ppm in the MCT footwall and 11-104 ppm in the LH dome gneisses) contents. Ba content varies from 222 to 640 ppm in the HH, 5 to 642 ppm in the MCT footwall and 208 to 542 ppm in the LH dome gneisses. The gneisses under consideration have a low Nb/Th ratio (0.38-1.2 in the HH, 0.28-2.23 in the MCT footwall and 0.5-1.78 in the LH dome gneisses), which is characteristics of crustal material. Other chemical characteristics i.e., high SiO2, low CaO and MgO contents, and peraluminous nature of the gneisses suggest that they are products of crustal melting. The Pl from the HH gneisses contains the highest concentration of anorthite component if compared with the Pl from the MCT footwall and the LH dome. The Mg# of Bt from the gneisses of the HH crystalline zone, MCT footwall, and LH dome varies from 0.35 to 0.5, 0.24 to 0.49, and 0.14 to 0.23, respectively. The Bt compositions of augen gneisses from all three zones plot in the field of Bt of peraluminous (including S-type) granite. The compositions of Ms from the MCT footwall plot in the field of secondary Ms of granitic rocks, while the Ms from the gneisses of the LH dome plot in the field of primary Ms in the Miller’s diagram. The Grt from the HH gneisses shows a retrograde zoning pattern, but that from the MCT footwall shows a prograde growth zoning pattern. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.9